Comparison of GeneXpert and line probe assay for the detection of Mycobacterium tuberculosis in direct sputum samples - R Lia Kusumawati; Mirzan Hasibuan; Tari, Nisrina; Kyaw Ko Ko Htet; Nyi Nyi Zayar (Indonesian Journal of Biomedicine and Clinical Sciences, 2025)
Tuberculosis (TB) remains a major global health issue, particularly in low-and- middle-income countries (LMICs) like Indonesia. Diagnostic methods for TB and multidrug-resistant TB (MDR-TB) such as Lowenstein-Jensen (LJ) solid media and Mycobacterium Growth Indicator Tube (MGIT), are time-consuming, causing delays in patient management. Rapid molecular diagnostics, like the GeneXpert MTB/RIF ultra assay and line probe assay (LPA), offer faster and more accurate detection of Mycobacterium tuberculosis and drug resistance. This study aimed to compare the efficacy of GeneXpert and LPA in detecting M. tuberculosis and assessing drug resistance in sputum samples from 20 patients with confirmed TB. The samples were categorized into four groups based on GeneXpert results: very low, low, medium, and high DNA concentration. GeneXpert identified 20% of samples as rifampicin-resistant, while LPA identified 35%. Additionally, LPA detected isoniazid resistance in 10% of samples. The five discordance results between GeneXpert and LPA, from samples with very low DNA concentrations, were confirmed using MGIT 960 culture DST as the gold standard. The LPA successfully identified 2 (10%) Hr-TB among TB cases detected by the GeneXpert TB/ RIF. While LPA demonstrates superior performance characteristics, particularly in detecting isoniazid, GeneXpert demonstrated better sensitivity and specificity, making it a more reliable diagnostic tool under suboptimal conditions, followed by culture-based DST to assure accuracy and examine resistance to other drugs.